Online e-tollgate fee collection using QRcode - Venkateswararao, Kuna; Gurusarathy, L; Sankar Reddy, Akepati (International Journal of Engineering and Technology, 2018)
Now a day’s People need to wait near the tollgate in queue for long time to pay the toll fee. The application on java is being introduced. Before we are reaching the tollgate it should display a message to the user that he is approaching the tollgate. The display of message based on GPS location. This Application helps to pay amount before the tollgate reached. Automatically it will generate an Electronic receipt with Barcode and QRcode in secure techniques .which can be shown at the tollbooth. This reduces the work of the people and the reduces the time. Payment is done through Mobile wallets or Credit cards. A list for all the tollgate and respective services to be made available in the application.